Waterproof consolidation coating as well as preparation method and coating method thereof

By coating the waterproof consolidation coating made of water glass solution and alkoxysilane on the loess block, the problem of deterioration of the performance of loess in water conservancy projects is solved, and the structural strength and waterproof performance of the loess block are significantly improved, which reduces the use of traditional building materials, and has both economic and environmental advantages.

CN119529573APending Publication Date: 2025-02-28SHAANXI WATER CONSERVANCY & ELECTRIC POWER SURVEY & DESIGN INSTITUTE (GROUP) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411699648.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In water conservancy projects, loess is prone to deterioration in performance after being subjected to water soaking, water flow erosion, dry and wet cycles and freeze-thaw cycles, resulting in reduced structural strength and accidents. At the same time, traditional cement, lime and other consolidated materials have high transportation and manufacturing costs, which are highly polluted to the environment.

Method used

A waterproof consolidation coating made of a mixture of water glass solution and alkoxysilane is coated on the surface of the loess block, and salt particles are generated through the exchange reaction between silicate and silica gel to enhance the surface strength; alkoxysilane forms a hydrophobic crosslinking network through self-polymerization, which improves the structural strength and waterproof performance of loess.

Benefits of technology

It significantly improves the friction resistance, hydrophobicity, water immersion resistance and freeze-thaw cycle resistance of loess blocks, enhances its comprehensive performance, reduces dependence on traditional building materials, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529573A_ABST
    Figure CN119529573A_ABST
Patent Text Reader

Abstract

The invention discloses a waterproof consolidation coating as well as a preparation method and a coating method thereof, belongs to the technical field of waterproof coatings, and can solve the problems that an existing material for improving the performance of loess is relatively high in transportation and manufacturing cost and relatively large in environmental pollution. The waterproof consolidation coating is formed by mixing a water glass solution and alkoxy silane; the water glass solution is formed by mixing silicate, silicic acid (H2SiO3) gel and water. The method is used for improving the comprehensive performance of the loess block.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a waterproof consolidation coating and a preparation method and a coating method thereof, belonging to the technical field of waterproof coatings. Background Art

[0002] Loess is distributed all over the world, including Asia, Europe, Africa, North America, and South America, and covers about 9.3% of the world's total land area. In my country, loess is the most common building material in northwestern provinces such as Shaanxi, Shanxi, Gansu, and Ningxia Hui Autonomous Region, and is widely used in the construction of local water conservancy projects such as silt dams. A silt dam is a water and soil conservation project built on the ditch in the Loess Plateau region of my country to intercept floodwaters, sediment, and reclaim land. Because loess is easy to obtain and easy to construct, loess is commonly used as the material for silt dam construction.

[0003] However, loess has the characteristics of metastable structure, high porosity, low plasticity, and high sensitivity to moisture. After being immersed in static water, eroded by water flow, wet-dry cycles, and freeze-thaw cycles, its performance deteriorates rapidly and seriously, resulting in a significant decrease in the structural strength of the silt dam, and serious accidents such as dam leakage, sliding, and collapse. In order to strengthen the structural performance of loess blocks, traditional building materials such as cement and lime are currently commonly used to consolidate loess, but these traditional building materials have defects such as high transportation and manufacturing costs and greater environmental pollution. Therefore, it is necessary to improve the structural strength and water resistance of the loess blocks themselves to reduce or avoid the use of traditional building materials and achieve both economic and environmental benefits. Summary of the invention

[0004] The invention provides a waterproof consolidation coating and a preparation method and a coating method thereof, which can solve the problems that the existing materials for improving the performance of loess have high transportation and manufacturing costs and cause great pollution to the environment.

[0005] In one aspect, the present invention provides a waterproof consolidation coating, wherein the waterproof consolidation coating is prepared by mixing a water glass solution and an alkoxysilane; The water glass solution is prepared by mixing silicate, silicate gel and water.

[0006] Optionally, the mass percentage of the water glass solution in the waterproof solidification coating is 5-95wt%.

[0007] Optionally, the mass percentage of the alkoxysilane in the waterproof solidification coating is 5~95wt%.

[0008] Optionally, the silicate is potassium silicate or sodium silicate.

[0009] Optionally, the alkoxysilane is dodecyltrimethoxysilane, hexadecyltrimethoxysilane or octadecyltriethoxysilane.

[0010] In another aspect, the present invention provides a method for preparing any of the above-mentioned waterproof consolidation coatings, the preparation method comprising: Mixing silicate, silicic acid gel and water to prepare a water glass solution; The water glass solution and alkoxysilane are mixed and stirred to prepare a waterproof solidifying coating.

[0011] Optionally, the water glass solution and alkoxysilane are mixed and stirred to prepare a waterproof solidifying coating, specifically: The water glass solution and the alkoxysilane are mixed and stirred for 1 to 60 minutes at a temperature of 15 to 35° C. and a rotation speed of 20 to 1000 r / min to prepare a waterproof solidifying coating.

[0012] At the same time, the present invention also provides a coating method of any of the above-mentioned waterproof consolidation coatings, the coating method comprising: Applying waterproof consolidation coating to the structure; Maintain the parts of the structure coated with waterproof consolidating paint.

[0013] Optionally, the waterproof consolidation coating is applied to the structure, specifically: Spray, brush, scrape or drip the waterproof solidifying paint on the structure.

[0014] Optionally, the maintenance of the portion of the structure coated with the waterproof consolidation coating is specifically as follows: The portion of the structure coated with the waterproof solidifying coating is cured at a temperature of 15 to 35°C for 5 to 10,000 minutes.

[0015] The beneficial effects that the present invention can produce include: The present invention utilizes water glass solution and alkoxysilane to prepare a waterproof consolidation coating. Since water glass has good hydrophilicity and alkoxysilane has excellent hydrophobicity, the two are combined to produce a synergistic effect. After being coated on the surface of the loess block, a waterproof consolidation layer of a certain thickness can be formed on the loess block, thereby greatly improving the friction resistance, hydrophobicity, resistance to pure water and salt water immersion, and resistance to freeze-thaw cycles on the surface of the loess block, thereby significantly enhancing the comprehensive performance of the loess block. Since the present invention is easier to manufacture and transport than traditional building materials such as cement and lime, and has less pollution to the environment, the application of the present invention can reduce or avoid the use of traditional building materials in loess water conservancy projects such as silt dams, which is conducive to achieving both economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a schematic diagram of the experiment for testing the permeability of waterproof consolidation coating in loess block samples; Figure 2 Schematic diagram of the penetration depth of waterproof consolidation coating in loess block sample; Figure 3 is the penetration depth of 3mL different waterproof consolidation coatings in the loess block sample; Figure 4 The weight wear residual rate of loess block samples coated with waterproof consolidation coatings of different proportions and different curing times; Figure 5 The water contact angle of the worn surface of the loess block sample coated with waterproof consolidation coatings of different proportions and different curing times; Figure 6 Scanning electron microscope (SEM) photos of the surfaces of different loess blocks, among which (a) is the SEM photo of the surface of the loess block without coating, (b) is the SEM photo of the surface of the loess block coated with water glass solution coating, (c) is the SEM photo of the surface of the loess block coated with alkoxysilane coating, and (d) is the SEM photo of the surface of the loess block coated with waterproof consolidation coating. DETAILED DESCRIPTION

[0017] The present invention is described in detail below in conjunction with embodiments, but the present invention is not limited to these embodiments.

[0018] The embodiment of the present invention provides a waterproof consolidation coating, which is prepared by mixing a water glass solution and an alkoxysilane; Water glass solution is a mixture of silicate, silicic acid (H2SiO3) gel and water.

[0019] Specifically, the silicate is potassium silicate (K2SiO3) or sodium silicate (Na2SiO3).

[0020] Specifically, the alkoxysilane is dodecyltrimethoxysilane, hexadecyltrimethoxysilane or octadecyltriethoxysilane.

[0021] Specifically, the mass percentage of the water glass solution in the waterproof consolidation coating is 5-95wt%. For example, it can be 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt% or 95wt%.

[0022] Specifically, the mass percentage of alkoxysilane in the waterproof consolidation coating is 5-95wt%. For example, it can be 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt% or 95wt%.

[0023] Specifically, the sum of the mass percentage of the water glass solution in the waterproof solidifying coating and the mass percentage of the alkoxysilane in the waterproof solidifying coating is 100wt%.

[0024] Another embodiment of the present invention provides a method for preparing any of the above-mentioned waterproof consolidation coatings, the preparation method comprising: Mixing silicate, silicic acid gel and water to prepare a water glass solution; The water glass solution and alkoxysilane are mixed and stirred to prepare a waterproof solidifying coating.

[0025] Specifically, the water glass solution and the alkoxysilane are mixed and stirred to prepare a waterproof solidifying coating, which can be: The water glass solution and the alkoxysilane are mixed and stirred for 1 to 60 minutes at a temperature of 15 to 35° C. and a rotation speed of 20 to 1000 r / min to prepare a waterproof solidifying coating.

[0026] For example, the stirring temperature can be 15°C, 20°C, 25°C, 30°C or 35°C; the stirring speed can be 20r / min, 50r / min, 100r / min, 200r / min, 500r / min or 10000r / min; the stirring time can be 1min, 5min, 10min, 20min, 30min, 45min or 60min.

[0027] Another embodiment of the present invention provides a coating method of any of the above-mentioned waterproof consolidation coatings, the coating method comprising: Applying waterproof consolidation coating to the structure; Maintain the parts of the structure coated with waterproof consolidating paint.

[0028] Specifically, before the waterproof consolidation coating is applied to the structure, the waterproof consolidation coating should be mixed and stirred evenly to avoid stratification.

[0029] Specifically, the waterproof solidifying coating can be applied by spraying, brushing, scraping or dripping.

[0030] Specifically, the waterproof consolidation coating is applied to the structure, which can be: Spray, brush, scrape or drip the waterproof solidifying paint on the structure.

[0031] Specifically, the maintenance of the part of the structure coated with the waterproof consolidation coating can be: The portion of the structure coated with the waterproof solidifying coating is cured at a temperature of 15 to 35°C for 5 to 10,000 minutes.

[0032] For example, the curing temperature can be 15°C, 20°C, 25°C, 30°C or 35°C; the curing time can be 5 min, 10 min, 20 min, 50 min, 100 min, 200 min, 500 min, 10000 min, 2000 min, 5000 min or 10000 min.

[0033] The numerical range described in the present invention includes not only the point values ​​listed above, but also any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention will no longer exhaustively list the specific point values ​​included in the range.

[0034] The present invention uses water glass solution and alkoxysilane to prepare a waterproof consolidation coating. The waterproof consolidation coating is coated on the surface of the loess block and then penetrates into the pores of the loess block. The silicate in the coating can be used as potassium ions (K + ) or sodium ion (Na + ) to exchange calcium ions (Ca 2+ ), magnesium ion (Mg 2+ ) and generate salt particles such as calcium silicate (CaSiO3) and magnesium silicate (MgSiO3) after dehydration, which enhance the strength, hardness and wear resistance of the surface of the loess block; silicic acid (H2SiO3) gel can fill the pores between the loess particles and greatly improve the connection strength between the loess particles, thereby improving the structural strength of the loess block; and the alkoxy group (-OR) in the alkoxysilane can react with the water molecules in the water glass solution and hydrolyze to form silanol. As an intermediate with high chemical reactivity, silanol will self-polymerize with each other. Silicanol can also react with the hydroxyl group (-OH) on the surface of the loess particles to form a silicic acid bond (-Si-O-Si-) cross-linked network, which plays a role in connecting the loess particles, thereby further improving the structural strength of the loess block. At the same time, the organic silicon group generated by the reaction also has good hydrophobicity, which can enhance the waterproofness of the surface of the loess block.

[0035] After the waterproof consolidation coating of the present invention is applied to the surface of the loess block, the surface structure of the loess block can be observed by scanning electron microscope (SEM). Figure 6As shown, it can be seen that the surface particles of the loess block not coated with paint have larger gaps, loose structure and lower strength; the surface particles of the loess block coated only with water glass solution paint or only with alkoxysilane paint are connected to each other, and its structural strength is enhanced compared with that when not coated with paint, but there are still large gaps between the particles; and the surface of the loess block coated with the waterproof consolidation paint described in the present invention forms a dense cross-linked network, the surface particles are connected to each other, the gaps are smaller, and the structural strength is significantly enhanced.

[0036] It can be seen from this that the waterproof consolidation coating described in the present invention can form a waterproof consolidation layer of a certain thickness on the loess block, thereby greatly improving the friction resistance, hydrophobicity, resistance to pure water and salt water immersion, and resistance to freeze-thaw cycles on the surface of the loess block, and can achieve a significant enhancement in the comprehensive performance of the loess block.

[0037] Since the present invention is easier to manufacture and transport than traditional building materials such as cement and lime, and has less pollution to the environment, the application of the present invention can reduce or avoid the use of traditional building materials in loess water conservancy projects such as silt dams, which is conducive to achieving both economic and environmental benefits.

[0038] For ease of understanding, the present invention lists several embodiments as follows to illustrate the waterproof consolidation coating and its preparation method and coating method described in the present invention.

[0039] Example 1: The mass percentage of water glass solution with potassium silicate (K2SiO3) and silicic acid (H2SiO3) gel as main components in the waterproof consolidation coating is 50wt%, and the mass percentage of dodecyltrimethoxysilane in the waterproof consolidation coating is also 50wt%; the stirring speed of the mixture of the two is 500r / min, the stirring time is 20min, and the stirring temperature is 25°C; the coating method is spraying; the curing temperature is 25°C, and the curing time is 1000min.

[0040] Example 2: The potassium silicate (K2SiO3) in Example 1 is replaced by sodium silicate (Na2SiO3), and the rest is the same as Example 1.

[0041] Example 3: The dodecyltrimethoxysilane in Example 1 is replaced by hexadecyltrimethoxysilane, and the rest is the same as Example 1.

[0042] Example 4: The dodecyltrimethoxysilane in Example 1 is replaced by octadecyltriethoxysilane, and the rest is the same as Example 1.

[0043] Example 5: The mass percentage of the water glass solution in the waterproof solidifying coating in Example 1 is replaced by 5wt%, and the mass percentage of dodecyltrimethoxysilane in the waterproof solidifying coating is replaced by 95wt%. The rest is the same as Example 1.

[0044] Example 6: The mass percentage of the water glass solution in the waterproof solidifying coating in Example 1 is replaced by 95wt%, and the mass percentage of dodecyltrimethoxysilane in the waterproof solidifying coating is replaced by 5wt%. The rest is the same as Example 1.

[0045] Example 7: The stirring speed in Example 1 is replaced with 20 r / min, and the rest is the same as Example 1.

[0046] Example 8: The stirring speed in Example 1 is replaced with 1000 r / min, and the rest is the same as Example 1.

[0047] Example 9: The stirring time in Example 1 is replaced with 1 min, and the rest is the same as Example 1.

[0048] Example 10: The stirring time in Example 1 is replaced with 60 min, and the rest is the same as Example 1.

[0049] Example 11: The stirring temperature in Example 1 is replaced with 15°C, and the rest is the same as Example 1.

[0050] Example 12: The stirring temperature in Example 1 is replaced with 35°C, and the rest is the same as Example 1.

[0051] Example 13: The coating method in Example 1 is replaced by brush coating, and the rest is the same as Example 1.

[0052] Example 14: The coating method in Example 1 is replaced by scraping, and the rest is the same as Example 1.

[0053] Example 15: The coating method in Example 1 is replaced by drip coating, and the rest is the same as Example 1.

[0054] Example 16: The curing temperature in Example 1 is replaced with 15°C, and the rest is the same as Example 1.

[0055] Example 17: The curing temperature of 25°C in Example 1 is replaced by 35°C, and the rest is the same as Example 1.

[0056] Example 18: The curing time in Example 1 is replaced with 5 minutes, and the rest is the same as Example 1.

[0057] Example 19: The curing time in Example 1 is replaced by 10000 min, and the rest is the same as Example 1.

[0058] In order to test the performance improvement of the waterproof consolidation coating on loess blocks, and compare the effects of various waterproof consolidation coatings with different proportions (i.e., different mass percentages of water glass solution and / or different mass percentages of alkoxysilane) and different curing conditions (i.e., different curing temperatures and / or different curing times), the present invention carried out the following performance tests on multiple loess block samples coated with different waterproof consolidation coatings.

[0059] 1. Permeability test of waterproof consolidation coating in loess block samples: Figure 1 As shown, a loess block sample without coating of 30mm×30mm×20mm in size was placed vertically in a petri dish, and its sides were sealed with polyvinyl chloride (PVC) film and adhesive. Then, 3mL of waterproof consolidation coating was dropped on the center of its 30mm×20mm upper surface by direct titration method, and allowed to penetrate downward naturally. After drying for 1 day in a laboratory environment, the loess block sample was cut vertically from the middle along the flat surface, and then an appropriate amount of deionized water was applied to the cross section. Since the part of the loess block sample immersed in the waterproof consolidation coating is hydrophobic, the penetration depth can be observed from the boundary between the dry and wet parts. d p ,like Figure 2 As shown. By conducting permeability tests on multiple loess block samples coated with different waterproof consolidation coatings, the penetration depths of different waterproof consolidation coatings in the loess block samples can be obtained. For example, water glass solution (PS) and dodecyltrimethoxysilane (WD10) are used to prepare waterproof consolidation coatings. By changing the mass percentage of dodecyltrimethoxysilane (WD10) in the waterproof consolidation coating, a variety of different waterproof consolidation coatings can be obtained. The penetration depths of different waterproof consolidation coatings in the loess block samples are shown in FIG. Figure 3 shown.

[0060] 2. Hydrophobicity test of loess block samples: drop a 4μL water droplet vertically on the upper surface of the loess block sample coated with a waterproof consolidation coating, and then immediately observe its water contact angle with a contact angle meter. The test uses the DSA100 contact angle meter of Kruss Company of Germany. The hydrophobicity test is performed on multiple loess block samples coated with different waterproof consolidation coatings to obtain the water contact angles of multiple loess block samples.

[0061] 3. Wear resistance (structural strength) test of loess block samples: Place the coated surface of the loess block sample coated with waterproof consolidation coating face down on the sanded surface of 200-mesh sandpaper, and then place a 200g metal sheet on the loess block sample as a weight to apply pressure to the contact surface between the loess block sample and the sandpaper. Then pull the sandpaper slowly and evenly from the bottom of the loess block sample to make the coated surface of the loess block sample rub against the sandpaper. Moving the sandpaper back and forth for 50cm each time is counted as one cycle, and a total of 50 cycles are tested. The weight of the loess block sample is weighed after 1, 5, 10, 25, and 50 cycles respectively. Repeat the test of 10 loess block samples for each waterproof consolidation coating, take the average value, and calculate the weight wear residual rate of the loess block sample after coating with this waterproof consolidation coating, and measure the water contact angle of the friction surface of the loess block sample after 50 cycles. By testing the wear resistance (structural strength) of multiple loess block samples coated with different waterproof consolidation coatings, the weight wear residual rate and water contact angle of the wear surface of the loess block samples after coating with different waterproof consolidation coatings can be obtained. For example, a waterproof consolidation coating is prepared with water glass solution (PS) and dodecyltrimethoxysilane (WD10), and a variety of different waterproof consolidation coatings can be obtained by changing the mass percentage of dodecyltrimethoxysilane (WD10) in the waterproof consolidation coating; after each waterproof consolidation coating is coated on the loess block sample, it is cured for 3 days and 7 days respectively, and the weight wear residual rate and water contact angle of the wear surface of the loess block sample after coating with different waterproof consolidation coatings and curing for different times can be obtained, such as Figure 4 and Figure 5 shown. Specifically, Figure 4 and Figure 5 The horizontal axis represents the number of the loess block sample. For example, the number PS means that the mass percentage of dodecyltrimethoxysilane (WD10) in the waterproof consolidation coating coated on the loess block sample is 0wt%, and correspondingly, the mass percentage of the waterglass solution (PS) is 100wt%; the number WD10 means that the mass percentage of dodecyltrimethoxysilane (WD10) in the waterproof consolidation coating coated on the loess block sample is 100wt%, and correspondingly, the mass percentage of the waterglass solution (PS) is 0wt%; the number PS-W10 means that the mass percentage of dodecyltrimethoxysilane (WD10) in the waterproof consolidation coating coated on the loess block sample is 10wt%, and correspondingly, the mass percentage of the waterglass solution (PS) is 90wt%; the number PS-W20 means that the mass percentage of dodecyltrimethoxysilane (WD10) in the waterproof consolidation coating coated on the loess block sample is 20wt%, and correspondingly, the mass percentage of the waterglass solution (PS) is 80wt%; the meanings of the remaining numbers are similar.

[0062] 4. Salt water resistance test of loess block samples: Multiple loess block samples coated with different waterproof consolidation coatings were placed in a mixed salt water solution containing 3wt% sodium chloride (NaCl) and 7wt% sodium sulfate (Na2SO4) at the same time. The liquid level of the solution was maintained at about 50mm above the upper surface of the immersed loess block sample. Adjacent loess block samples were spaced more than 10mm apart to eliminate interference with each other. The solution was kept in a laboratory environment and replaced every 3 days. Every 5 days, the loess block samples were fished out and observed for cracks or disintegration on the surface and then put back. After 30 days, all loess block samples were taken out and dried in a laboratory environment for 7 days, and their surface weathering was observed.

[0063] 5. Water resistance test of loess block samples: Place multiple loess block samples coated with different waterproof consolidation coatings into multiple beakers filled with 1L of distilled water, and the liquid level of the solution is maintained at about 150mm above the upper surface of the immersed loess block sample. Each loess block sample is placed separately in a different beaker to eliminate interference with each other. The evaporated water is replenished every 5 days to keep the liquid level basically unchanged. The loess block samples are fished out on the 1st, 7th, 15th and 30th days, respectively, and their surfaces are covered with absorbent paper. After absorbing the surface moisture, they are weighed to calculate their water absorption and weight gain rate. At the same time, the corresponding time of particle shedding, wet collapse and block disintegration on the surface of the loess block sample is recorded, and then put back. After 30 days, all loess block samples are taken out, their water contact angles are measured and reserved for subsequent freeze-thaw resistance tests.

[0064] 6. Freeze-thaw resistance test of loess block samples: After wiping the surface of the loess block sample that has undergone a 30-day water resistance test with absorbent paper, place it in a 20°C environment for 12 hours, and then place it in a -20°C environment for 12 hours, which is recorded as one cycle. After a total of 30 cycles, thaw it in a laboratory environment for 6 hours, and then observe its surface integrity and the condition of surface particle shedding and block disintegration. If particle shedding or even block disintegration has occurred before 30 cycles, record the corresponding number of cycles.

[0065] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A waterproof consolidation coating, characterized in that: The waterproof consolidation coating is formed by mixing a water glass solution and an alkoxysilane; The water glass solution is prepared by mixing silicate, silicate gel and water.

2. The waterproof consolidation coating according to claim 1, characterized in that: The mass percentage of the water glass solution in the waterproof solidifying coating is 5-95wt%.

3. The waterproof consolidation coating according to claim 1, characterized in that: The mass percentage of the alkoxysilane in the waterproof solidification coating is 5-95wt%.

4. The waterproof consolidation coating according to claim 1, characterized in that: The silicate is potassium silicate or sodium silicate.

5. The waterproof consolidation coating according to claim 1, characterized in that: The alkoxysilane is dodecyltrimethoxysilane, hexadecyltrimethoxysilane or octadecyltriethoxysilane.

6. A method for preparing the waterproof consolidation coating according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Mixing silicate, silicic acid gel and water to prepare a water glass solution; The water glass solution and alkoxysilane are mixed and stirred to prepare a waterproof solidifying coating.

7. The preparation method according to claim 6, characterized in that: The water glass solution and alkoxysilane are mixed and stirred to prepare a waterproof solidifying coating, specifically: The water glass solution and the alkoxysilane are mixed and stirred for 1 to 60 minutes at a temperature of 15 to 35° C. and a rotation speed of 20 to 1000 r / min to prepare a waterproof solidifying coating.

8. A method for coating the waterproof consolidating coating according to any one of claims 1 to 5, characterized in that: The coating method comprises: Applying waterproof consolidation coating to the structure; Maintain the parts of the structure coated with waterproof consolidating paint.

9. The coating method according to claim 8, characterized in that: The waterproof consolidation coating is applied to the structure, specifically: Spray, brush, scrape or drip the waterproof solidifying paint on the structure.

10. The coating method according to claim 8, characterized in that The maintenance of the part of the structure coated with the waterproof consolidation coating is specifically as follows: The portion of the structure coated with the waterproof solidifying coating is cured at a temperature of 15 to 35°C for 5 to 10,000 minutes.

Citation Information

Patent Citations

  • Organic-inorganic hybrid solution type water repellent for surfacers of building materials and preparation process thereof

    CN102701788A

  • High-antifouling inorganic silicate paint containing organosilicone, and preparation method and application thereof

    CN106084925A

  • Breathable permeable concrete protective agent and preparation method thereof

    CN115043612A

  • Silicate waterproof coating and preparation method thereof

    CN118240406A

  • Method of consolidating poor quality soils

    KR1019800001254B1